Women Self-Defense and Security System - Pokhrel, Richa; Jha, Asmita; Singh, Pooja; Jha, Pragya; Bastola, Rama (Journal of Innovations in Engineering Education, 2020)
The main objective of our project is to provide security for human beings especially woman and children with a help of an advanced electronics. As most of the women are subjected to unethical physical harassment when they are alone in public areas, in case they will be provided with an equipment fitted inside the shoes which is not visible to others, the equipment consists of GPS (Global Positioning System) and GSM module by which the geographical location can be tracked and can be sent. In the case of any emergency conditions, the button is pressed and the microcontroller sends latitude and longitude information to authorized persons through GSM. Then the location information is tracked and the information can be sent to police and family members so that they can be rescued in proper time. At the same time, they will be provided a high voltage generating device embedded within the system can be used to generate electric shock to temporarily paralyse the criminals in critical situations. The device is portable and hence can be taken anywhere we travel. It is economical and simple to use. So, it can be effective in saving many people (not merely women) from criminal attacks, sexual harassments and can be used as legal evidence of crime.